Comparison between chronological and dental ages according to three estimation methods in a Peruvian population - Quito, Liz Mónica Perales (2022)
Dental age estimation techniques have great importance in dental evaluation, specifically in the orthodontic, academic, and forensic areas. The aim of this study was to compare the dental age according to the Demirjian, Nolla and Cameriere methods with the chronological age in a Peruvian population. This is an observational, descriptive, retrospective and cross-sectional study, which had a total population of 578 panoramic radiographs of subjects aged 6 to 14 years, where the difference in means from a previous study was calculated, and 193 subjects were finally randomly selected. The chronological ages (CA) and dental ages (DA) were compared using the Wilcoxon and Kruskall Wallis Range Tests. The means were 8.77 ± 2.34 and 8.90 ± 2.04 years of the CA for the female and male genders, respectively. The difference in means of the CA and DA according to the Nolla, Demirjian and Cameriere methods were-0.38, 0.96 and-0.21 years, respectively, for the total study sample. A positive correlation was found for the three methods studied; however, the Demirjian method showed a statistically significant difference with an underestimation of-0.91 years in the total sample. Also, the method of Cameriere was the closest to the chronological age.